FAKTOR FAKTOR YANG MEMPENGARUHI MASYARAKAT MEMILIH PENGOBATAN ALTERNATIF DIKECAMATAN KOTA BARAT KOTA GORONTALO UNIVERSITAS MUHAMMADIYAH GORONTALO - Anik Indarwati; Ani Retni (program studi ilmu keperawatan fakultas ilmu kesehatan universitas muhammadiyah gorontalo, 2021)
Factors affecting society choose alternative medication in Kota Barat District. Tthe aim of this research is to the factors that affect society to choose alternative medication .this type of research is used observasional analytic with cross sectional approach .the number of population 6,076 households and the number of responden in a sample are 120 hounseholds.the analysis of data is used univariat,bivariat,and multivariate analysis These results are that (a) Social factors had an effect on society decision to choose alternative medication in kota barat distric with a value of 0.000, (b) economic .Faktor also efectif on society decision to choose the decision of the choose alternative medicine in kota barat District with a value of 0.000 (c) .Faktor of culture also had an affect on social to choose alternative medicine in kota barat District with a value 0.015,based on the three factors are researched, the more effection factor is the social and cultural factors. That a correlation rate of 0.472.